Incidental image memorability. Issue 9 (21st October 2019) - Goetschalckx, Lore; Moors, Jade; Wagemans, Johan
ABSTRACT: Recent studies using intentional memory tasks showed that images differ consistently in memorability. Here, we used a surprise recognition memory test. We asked how incidental encoding would affect the consistency and ranking of the memorability scores. If memorability is truly an intrinsic property of the image, one should not expect large differences between incidental and intentional conditions. On the other hand, participants might process images differently when not anticipating a memory test, yielding different results. The study list of our incidental memory task was identical to our previous, intentional study. Participants were to watch the images of this list carefully as they appeared on the screen one by one (free viewing); supposedly for a study about eye movements. Afterwards, a surprise recognition memory test was administered. Despite the free viewing instructions during the study phase, the resulting incidental image memorability scores still showed high levels of consistency across participants. In addition, the overlap between the incidental and intentional memorability ranking was large. These results provide further support for the idea of memorability as an intrinsic image property and add to its ecological validity, as people rarely memorise images intentionally.